The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jsbm.12389
|View full text |Cite
|
Sign up to set email alerts
|

Socioemotional Wealth and Innovativeness in Small- and Medium-Sized Family Enterprises: A Configuration Approach

Abstract: What makes small‐ and medium‐sized family firms (family SMEs) innovative? Some family firm dynamics promote, yet others hinder innovation. It remains unclear whether combinations of family firm dynamics increase innovativeness. Our configurational perspective of socioemotional wealth (SEW) unravels determinants of family SMEs' innovativeness. We conduct a fuzzy set qualitative comparative analysis with 452 Swiss family SMEs. We categorize SEW dimensions into configurations of necessary and sufficient condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 84 publications
(131 reference statements)
1
40
0
Order By: Relevance
“…We extend the applicability of social capital theory in a more specific compendium of corporate social responsibility (CSR) and in the family business context. The discovery of novelty in these MSEW dimensions offers new insights on environmental strategy in the family business, by incorporating the mediating function of capabilities, hence enriching the current literature on the role of MSEW as an antecedent Fitz-Koch & Nordqvist, 2017;Gast et al, 2018) in family business theory.…”
Section: Discussionmentioning
confidence: 97%
“…We extend the applicability of social capital theory in a more specific compendium of corporate social responsibility (CSR) and in the family business context. The discovery of novelty in these MSEW dimensions offers new insights on environmental strategy in the family business, by incorporating the mediating function of capabilities, hence enriching the current literature on the role of MSEW as an antecedent Fitz-Koch & Nordqvist, 2017;Gast et al, 2018) in family business theory.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, only a few previous studies have addressed the SEW dimensions and their measurement. Gast et al (2018) identified five dimensions congruent with the FIBER scale. Contrary to the aforementioned results, our empirical data show support for a three factor solution combined by family control and identification with the firm, binding social ties, and renewal of family bonds and emotional attachment of family members.…”
Section: Discussionmentioning
confidence: 97%
“…The configurational design has accommodated the complexity of firm performance (MacDougall, Bauer, Novicevic, & Buckley, 2014) and equifinality (Fiss, 2011). For example, Gast et al (2018) argue that individual SEW dimensions are not inherently negative or positive. They suggest five causal configurations of SEW dimensions, showing how their combined effects influence family firm innovativeness.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating different innovation levels (i.e., sustaining or disruptive) blurs the picture even more and adds to the already existing complexity and ambivalence of family influence on family firm innovation. A recurring finding in the wider family firm innovation literature is that family firms innovate incrementally rather than radically (Calabrò et al 2019;Nieto et al 2015;Roessl et al 2010) and have less incentive to pursue disruptive innovations (Gast et al 2018;Kraus et al 2018). It is suggested that this is because family firms tend to focus on SEW preservation (Filser et al 2018), avoid risk-taking to protect wealth (De Massis et al 2014), have poorly developed innovation capabilities (Sciascia et al 2015), and exhibit family entrenchment (Anderson and Reeb 2003) and family orientation lock (Herrero and Hughes 2019).…”
Section: Disruptive Innovation and The Family Firmmentioning
confidence: 99%